Effect of Denosumab Therapy on Pain Level in Diffuse Sclerosing Osteomyelitis of the Mandible: a Case Report - Daniel Jerković; Kristian Jerković; Antonella Lesin; Ana Poljičanin; Ivan Galić (University of Zagreb. School of Dental Medicine, 2023)
This is the first case report where two patients were under uniform denosumab administration protocol in diffuse sclerosing osteomyelitis (DSO) treatment and were closely monitored for 18 months. Objectives: This study aimed to describe the beneficial effects of denosumab in DSO treatment as well as pain relief and the significant lack of long-term use due to poorer outcomes after repeated use. DSO of the jaw is a poorly understood rare chronic disease the treatment of which is still very challenging despite a rapid development of medicine. Different medical treatments have been pro-posed without any significant long-lasting success. Bisphosphonates have offered substantial clinical benefit in DSO therapy, but due to harmful pharmacodynamic properties, denosumab therapy has been used to replace bisphosphonate therapy. Patients had a reduction in pain intensity with each subsequent application of denosumab but with less success than the first administration of de-nosumab. This case report has shown that denosumab could be a promising conservative treatment option for pain treatment in patients suffering from DSO.